Epimedium brevicornum Maxim alleviates diabetes osteoporosis by regulating AGE-RAGE signaling pathway - Shan Shan Lei; Yu Yan Wang; Xiao Wen Huang; Xu Ping Wang; Ming Gao; Bo Li (Molecular Medicine)
Abstract Objectives Epimedium brevicornum Maxim (EP) has a history of utilization in Chinese traditional medicine for the treatment of bone diseases. However, the precise mechanism by which EP extract (EPE) operates in Diabetes osteoporosis (DOP) remains ambiguous. The study was aimed to explore the effects and underlying mechanisms of EPE on DOP, with particular emphasis on the AGE-RAGE pathway. Methods The DOP model was induced through a combination of a high-sugar and high-fat diet along with streptozotocin injection. Following treatment with EPE, blood glucose levels, body weight, and serum biomarkers were measured. The trabecular microstructure of the femur was analyzed using micro-CT tomography and H&E staining. Bioinformatics techniques, including network pharmacology and molecular docking, were utilized to identify key targets of EP for DOP. The predicted targets and pathways were further validated through RT-PCR, TSA analysis ELISA, and western blotting (WB), respectively. Results The findings from animal experiments indicate that EPE has a positive impact on weight and blood glucose levels, particularly in reversing the decrease and disordered arrangement of bone trabeculae. Bioinformatics analysis reveals the involvement of the AGE-RAGE pathways in the treatment of DOP with EPE. Subsequent animal validation experiments demonstrate that EPE can regulate key proteins AGE-RAGE pathway, resulting in reducing the inflammatory factors and apoptosis, including advanced Glycation End-products (RGEs), receptor for Advanced Glycation End-products (RAGE), Interleukin-6 (IL-6), Interleukin-1β (IL-1β), Nuclear Factor Kappa B (NF-κB), BCL2-Associated X protein (Bax), B-cell lymphoma 2(Bcl2), and etc. Conclusion This study provides clear evidence that EPE mitigates DOP through enhancement of the AGE-RAGE pathways, offering innovative insights and approaches for clinical utilization. Graphical abstract